2022
DOI: 10.1002/dro2.28
|View full text |Cite
|
Sign up to set email alerts
|

A functionalized ionic liquid as the next‐generation nano‐lubricant

Abstract: Ionic liquids (ILs) have attracted intensive research interest due to their outstanding physiochemical properties. However, comprehensive design is necessary for targeted applications and has rarely been conducted. As a result, the industry‐scale application of ILs is still very limited. In this academia–industry collaborative research among the University of Pittsburgh, Virginia Tech. University, and Seagate Technology LLC, we report the design, synthesis, molecular dynamics (MD) simulation, and characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…65 In 2022, Wang et al reported a nanoscale ionic liquid with better thermal stability compared to perfluoropolyether, able to tolerate high temperatures approaching 300 °C. 137 (3) SLIPS also has a problem that the use of lubricants may pollute the environment. For example, some lubricants used in SLIPSs are fluorinated liquids, which might be hardly degraded and harmful to the organism, so it is necessary to find more eco-friendly and biocompatible substitutes to replace them.…”
Section: Discussionmentioning
confidence: 99%
“…65 In 2022, Wang et al reported a nanoscale ionic liquid with better thermal stability compared to perfluoropolyether, able to tolerate high temperatures approaching 300 °C. 137 (3) SLIPS also has a problem that the use of lubricants may pollute the environment. For example, some lubricants used in SLIPSs are fluorinated liquids, which might be hardly degraded and harmful to the organism, so it is necessary to find more eco-friendly and biocompatible substitutes to replace them.…”
Section: Discussionmentioning
confidence: 99%